A comparative profitability analysis of rice production under the anchor borrowers’ programme for rice farmers association of Nigeria (RIFAN) in Kaduna State, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
The Central Bank of Nigeria Anchor Borrowers’ Programme (ABP) since 2015 has provided huge support to rice farmers in Nigeria in terms of input supply through the Rice Farmers Association of Nigeria, with the intent to boost rice production. This study carried out a comparative profitability analysis of lowland rice production among beneficiaries and non-beneficiaries of the Anchor Borrowers’ Programme in Kaduna State. 220 respondents were selected using multistage sampling techniques from six communities in Chikun, Kaduna South, and Igabi Local Government Areas, where the two (2) categories of lowland rice farmers with farm sizes of 0.5 ha and above were randomly selected. Descriptive statistics, multiple regression analysis, and net farm income were used in analyzing the data collected for the study. The findings revealed that sex, farming experience, rice farm size, and extension contact were factors that influenced the output of RIFAN beneficiaries of the ABP, while level of education, rice farm size, membership in a cooperative, and extension contact were variables that influenced the rice output of non-beneficiary rice farmers of the ABP. The gross margins of RIFAN member beneficiaries and non-beneficiaries of ABP were N116,019.00 and N114,016.9, respectively, with a net farm income of N104,831.20 and N103,566.30, respectively. The return on investment for RIFAN member beneficiaries and non-beneficiary of the ABP were N 1.5k and  N1.59k, respectively, with no significant difference between the net incomes for both categories of farmers.
Keywords: Beneficiaries; Income; Output; Net Farm; Revenue